Floristic composition of a conservation area in the Federal District of Brazil - Silva, Juliana Silvestre (2012)
Cerradão vegetation shares many species with savanna and forest areas and is one of the most vulnerable phytophysiognomies in the Cerrado (Brazilian savanna) biome. The floristic composition of the Cerradão Biological Reserve was examined between September/2007 and November/2008. A total of 282 species distributed among 194 genera and 75 families were encountered, demonstrating proportions of 0.91 herbaceous species and 0.54 shrub species for each tree species. Fabaceae, Asteraceae, Rubiaceae, Poaceae, Myrtaceae, Malpighiaceae, and Melastomataceae were the most species-rich families. Fully 72.3% of the species of this dystrophic cerradão were shared by cerrado and forest vegetations, while 60.43% were shared by other cerradão sites, although the largest proportion of species (91%) were shared with cerrado sensu stricto. No species was found to be exclusive to this cerradão site, but approximately 95% of all species were native to the Cerrado biome.